PT Bank Negara Indonesia Tbk Menangkan ASRRAT 2024 Melalui Akuntansi Keberlanjutan yang Mendorong Transformasi Hijau (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the implementation of sustainability accounting at PT Bank Negara Indonesia (Persero) Tbk (BNI) as a strategic tool to support green transformation and the realization of sustainable development. Through a qualitative case study approach, the research analyzes how BNI integrates Creating Shared Value (CSV), Social Return on Investment (SROI), and Environmental, Social, and Governance (ESG) principles into its business strategy to generate simultaneous economic, social, and environmental value. The results show that BNI’s sustainability accounting is not merely a reporting obligation but serves as a core mechanism in evaluating and directing business practices toward long-term sustainable goals. BNI has successfully implemented various sustainability initiatives, such as green financing, empowerment of micro, small, and medium enterprises (MSMEs), climate risk stress tests, and digital financial inclusion programs, all of which demonstrate measurable contributions to the Sustainable Development Goals (SDGs). The bank’s achievement in obtaining the Gold Rank at the Asia Sustainability Reporting Rating (ASRRAT) 2024 affirms the effectiveness of its sustainability strategy. This research highlights the importance of embedding sustainability accounting within the company’s governance and operational structure and recommends that future studies expand to cross-sectoral comparisons for broader generalization. Furthermore, this study provides practical insights for companies aiming to adopt sustainability accounting as an instrument of strategic transformation rather than administrative compliance.